Global prediction of the energy yields for hybrid perovskite/Si tandem and Si heterojunction single solar modules. (29th April 2022) - Kato, Yoshitsune; Katayama, Hirotaka; Kobayashi, Tomoya; Kozawa, Masayuki; Nishigaki, Yukinori; Kobayashi, Tomonao; Kinden, Yosuke; Oiwake, Kohei; Ishihara, Ryo; Matsui, Taisuke; Aya, Youichirou; Hashiguchi, Taiki; et al.
Abstract: A strong expectation exists for a two‐terminal hybrid perovskite/silicon tandem solar cell for generating substantially higher output power. Nevertheless, a high tandem cell efficiency under the standard condition does not guarantee high power generation in outdoor environment due to the requirement of current matching in a tandem device. Here, we predict the global energy yields of hybrid perovskite/Si tandem and Si heterojunction single modules by establishing a new rigorous self‐consistent model that performs full device simulations incorporating all fundamental time‐varying parameters affecting the module power output. In particular, the temperature dependences of the optical and electrical characteristics are modeled explicitly and reliable model parameters are extracted from an industry‐compatible Si heterojunction single cell (23.27% efficiency with a 120 μm wafer thickness), whereas ideal cell characteristics are assumed for a hybrid perovskite top cell. Our simulation approach is justified from the remarkable agreement with experimental results. We find that the tandem architecture improves a module energy yield in all places by a maximum of 1.6 times, compared with a state‐of‐the‐art Si heterojunction single module. Importantly, the annual energy yields of the tandem and single modules scale linearly with annual sun irradiation, even with the requirement of the current matching in the case of the tandem device, and the ratio of the tandem and single energy yields is governed essentially by the module efficiency ratio obtained under standard conditions. We have further revealed the climate‐dependent energy yield variation with a magnitude of ~5% based on Köppen‐Geiger climate classification. Moreover, the optimization of the top‐cell band gap based on real meteorological data shows that the optimum top‐cell gap needs to be increased at a place with a lower solar irradiation. Abstract : The global energy yield of hybrid perovskite/Si tandem modules is predicted based on a self‐consistent rigorous calculation, showing very high module power outputs over the globe compared with a state‐of‐the‐art Si heterojunction module, even though precise current matching is required for the tandem module.